2005
DOI: 10.1039/b414654a
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the photophysical properties of indoprofen photoproducts in relation with their DNA photosensitizing properties

Abstract: The photophysical properties of indoprofen photoproducts have been examined in various solvents by absorbance and emission spectroscopies in relation with their photosensitizing properties. The photophysical properties of 2-[4-(1-hydroxy)ethylphenyl]isoindolin-1-one (HOINP) and 2-(4-ethylphenyl)isoindolin-1-one (ETINP) are typical of a singlet excited state when the ones of 2-(4-acetylphenyl)isoindolin-1-one (KINP) are based on its triplet excited state according to previous work. The effect of solvent polarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In the case of TTET in DNA, major differences in photosensitization mediated by either a parent compound or its photoproducts have been reported. [45,46] Once the conditions for linearity had been established, we could compare the efficiency of the different photosensitizers at inducing CPDs in DNA. Drastic differences were observed, even for the same class of photosensitizers.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of TTET in DNA, major differences in photosensitization mediated by either a parent compound or its photoproducts have been reported. [45,46] Once the conditions for linearity had been established, we could compare the efficiency of the different photosensitizers at inducing CPDs in DNA. Drastic differences were observed, even for the same class of photosensitizers.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been previously demonstrated that the photosensitizing properties of KP and other benzophenone derivatives in DNA depend mainly on the benzophenone chromophore [8]. The involvement of photoproducts in DNA photosensitization processes was already reported for some NSAIDs [17][18][19]. From a chemical point of view, the alkali-labile lesion to DNA photosensitized, via an electron transfer mechanism, appears to be a redox reaction between DNA and the excited state of the photosensitizer.…”
Section: Introductionmentioning
confidence: 94%
“…16 Recently, they reported that the photophysical properties of INP photoproducts correlated with their DNA photosensitizing properties. 17 A rapid and sensitive RPLC-based analytical procedure was previously described by Lakings et al, 18 which was proved effective for the simultaneous measurement of INP and its acidic and basic degradants in human milk. However, the applicability of existing RPLC methods for measurements of INP in samples containing photodegradants of this agent was uncertain.…”
Section: Introductionmentioning
confidence: 99%